A posteriori error estimation for discontinuous Galerkin discretizations of H(curl)-elliptic partial differential equations - Houston, Paul; Perugia, Ilaria; Schoetzau, Dominik (2005)
We develop the a posteriori error estimation of interior penalty discontinuous Galerkin discretizations for H(curl)-elliptic problems that arise in eddy current models. Computable upper and lower bounds on the error measured in terms of a natural (mesh-dependent) energy norm are derived. The proposed a posteriori error estimator is validated by numerical experiments, illustrating its reliability and efficiency for a range of test problems.